Understanding the Role of T-Cells in the Antimyeloma Effect of Immunomodulatory Drugs - D'Souza, Criselle; Prince, H. Miles; Neeson, Paul J. (Frontiers in Immunology, 2021)
Immunomodulatory drugs (IMiDs) are effective treatments for patients with multiple myeloma. IMiDs have pleotropic effects including targeting the myeloma cells directly, and improving the anti-myeloma immune response. In the absence of myeloma cells, lenalidomide and pomalidomide induce CD4+ T cell secretion of IL-2 and indirect activation of Natural Killer (NK) cells. In the context of T cell receptor ligation, IMiDs enhance T cell proliferation, cytokine release and Th1 responses, both in vivo and in vitro. Furthermore, combination treatment of IMiDs and myeloma-targeting monoclonal antibodies eg. daratumumab (anti-CD38) and elotuzumab (anti-SLAMF7), checkpoint inhibitors, or bispecific T cell engagers showed synergistic effects, mainly via enhanced T and NK cell dependent cellular toxicity and T cell proliferation. Conversely, the corticosteroid dexamethasone can impair the immune modulatory effects of IMiDs, indicating that careful choice of myeloma drugs in combination with IMiDs is key for the best anti-myeloma therapeutic efficacy. This review presents an overview of the role for T cells in the overall anti-myeloma effects of immunomodulatory drugs.